Peran Guru PAK Dalam Memberi Pemahaman Yang Benar Tentang Penggunaan Media Sosial Dan Penerapannya Di SMK Negeri 1 Ngabang - Mau, Marthen; Sander, Relly; Gianto, Gianto; Keluanan, Yane Henderina (Jurnal Teologi dan Pendidikan Kristen, 2024)
Some students at SMK Negeri 1 Ngabang, when the Covid-19 pandemic hit the world, students were required to study from home, so the opportunity was misused in using social media. The mistake in using social media is posting oneself via TikTok, dressing inappropriately, smoking, and other impolite actions. The aim of this research is to provide students with a correct understanding of how to use social media responsibly. The research methodology used is qualitative research using observation, interview and literature data collection techniques. The results found are that if PAK teachers concentrate more on providing a correct understanding of the use of social media, then students will become more responsible in using social media, both for business purposes, education, and getting and conveying information online. Conclusion: students at SMK Negeri 1 Ngabang have realized that using social media correctly will bring great benefits to all parties, including those who faithfully use social media in various applications.